Sessualità, riproduzione e costruzione di soggettività femminili “moderne” nelle scuole di Mekelle (Tigray-Etiopia) - Adami, Désirée (Antropologia Pubblica, 2024)
In the field of politics and development, the inversely proportional link between education and pregnancy receives great attention. Worldwide the most educated women give birth to fewer children and later than their less educated peers. The school is considered to provide that technical-scientific knowledge transforming women from “victims of tradition” to autonomous and rational subjects who give birth by choice, thus electing the school as a privileged path to exit from poverty. This article explores the rhetorical and practical processes of subjectivation activated in the high schools of Mekelle (Tigray-Ethiopia). Here the scientific rationality of books plays a marginal role with respect to the reproductive agency of those who continue in the study. Rather, educated women embody a pattern of “good femininity” focused on a normative order of events where sexual activity, marriage and motherhood (the two main institutions which guarantee(d) a passage of status and a full social recognition as mature women) must follow the educational and job career (Johnson-Hanks 2006). A corollary of the constant process of making formal education and reproductivity so closely intertwined is the fact that much of this rhetoric rests on strongly ideological grounds. It is thinking of themselves as “moral agents” in a modern state, that young female students build a sense of dignity and personal success, and it is this sense that makes lower fertility possible. The formal education puts urban and educated women on a path of distancing themselves from traditional certainties towards a more modern but also more uncertain future.